Determination of polycyclic aromatic hydrocarbons in grilled chicken and beef and their bioaccessibility using in vitro human digestion model - Hamidi, Elliyana Nadia (2015)
Bioaccessibility of contaminant in food is defined as the fraction of the contaminant that is released from food matrix in the gastrointestinal tract and thus become available for intestinal absorption. As an important human exposure pathway of contaminants, dietary intake of polycyclic aromatic hydrocarbons (PAHs) is of increasing concern for assessing health risk in human body. Therefore, the present study aimed to evaluate the bioaccessibility of PAHs in different parts of digestive system and to determine the effect of degree of doneness and fat content on the bioaccessibility of PAHs in grilled meat. In this study, the bioaccessibility of PAHs was assessed using in vitro human digestion model of grilled beef and chicken (satay). The samples were prepared by charcoal grilling and the levels of 15 prioritycontrolled PAHs in the samples were determined using high performance liquid chromatography (HPLC) equipped with photodiode array detector and fluorescence detector. The level of PAHs in the liquid portion of the digested samples were compared to the level in the undigested samples to determine the percentage of PAHs released i.e. its bioaccessibility. Limit of detection (LOD) of PAHs compounds were ranged from 0.025 to 5.0 ng/g, while limit ofquantification (LOQ) were ranged from 0.075 to 15.0 ng/g. Recovery of PAHs was varied in the range 13.68 to154.6% and 43.37 to 144.79% for beef and chicken samples, respectively. In general, there were significant differences (p<0.05) in PAHs bioaccessibility in different parts of digestive system with higher in stomach part as compared in mouth and small intestine parts of both grilled samples. The bioaccessibility of PAHs were ranged from 3.4% to 96.79% in stomach, 3.18% to 60.44% in mouth and 2.38% to 81.02% in small intestine of grilled meat; while 7.36% to 83.67% in stomach, 0.67% to 51.13% in mouth and 1.26% to 63.55% in small intestine of grilled chicken. There were also significant differences (p<0.05) in bioaccessibility of PAHs with increased degree of doneness in both grilled beef and chicken. Bioaccessibility of PAHs was higher in well done cooked than in rare and medium cooked meat. Results indicated that the bioaccessibility of PAHs ranged from 2.38% to 43.75% in rare, 5.27 to 79.02%in medium, and 6.51% to 84.83% in well done cooked grilled beef; 0.67% to 8.93% in rare, 1.3% to 21.28% in medium and 2.95% to 21.87% in well done cooked grilled chicken. In addition, there was also a positive correlation (R2 = 0.923) between fat content and bioaccessibility of PAHs in both meat samples. In sum, this study pointed out the importance of food matrix (beef and chicken meat), elemental chemical properties (pH,enzyme) in different part of digestive system, physicochemical (polarity, water solubility) and cooking practices (rare, medium and well done) in the bioaccessibility of PAHs.